UTILIZATION OF SOFTWARE SUPPORT IN EDUCATIONAL PROCESS - FECHOVÁ, Erika (Trends in education, 2012)
Effectiveness of educational process can be increased by the application of some modern forms of teaching. One of them is implementation of information and communication technologies into teaching and utilization of inter-subject relations. The paper deals with the possibility of utilization of software support at innovative approach to the solution of the physical problem from electronics.
Keywords: information and communication technologies; RLC series circuit; differential equation; MATLAB; Mathematica.